Pengaruh Working Capital Turnover, Perubahan Laba, dan Sales Growth Terhadap Financial Distress (Studi Empiris pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Mafiroh, Siti; Mu'arif, Syamsul (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
As an investor, before investing in a company, you need complete and accurate company information regarding the company's financial condition. This aims to enable investors to obtain dividends on the funds they invest in the company. This research will discuss financial distress. Financial distress is a condition of economic difficulty or financial crisis experienced by a company before bankruptcy occurs. This research aims to determine the influence of Working Capital Turnover, Profit Changes, and Sales Growth on Financial Distress. Empirical Study of Non-Cyclical Consumer Companies Listed on the Indonesian Stock Exchange (BEI) in 2019-2023. The type of research used is quantitative research using secondary data in the form of financial reports of Consumer Non-Cyclicals companies obtained from the official website of the Indonesia Stock Exchange (BEI) and the official websites of each company. The selected samples were 24 companies with observations for 5 years in the 2019-2023 period or 120 samples based on the pursive sampling method. The analysis technique used in this research uses panel data regression analysis with the help of Eviews 12 data processing software. The research results show that Working Capital Turnover, Profit Changes and Sales Growth simultaneously influence Financial Distress. Working Capital Turnover partially has a negative effect on Financial Distress, Profit Changes have no effect on Financial Distress, and Sales Growth partially has no effect on Financial Distress.